Del.icio.us development tools - DeLIne, Robert (CHASE '08: Proceedings of the 2008 international workshop on Cooperative and human aspects of software engineering, 2008)
Developers need better knowledge tools to answer their information needs, rather than continuing to rely so heavily on communication with coworkers. Web sites, like the social bookmarking site Del.icio.us, might provide a way forward. They are designed to provide each user an individual incentive for entering data, but provide even more value by combining data from different users into collective knowledge. Several research projects hint that designing knowledge tools for developers using this principle would be more cost effective and provide better incentive structures for capturing knowledge.